2018
DOI: 10.1155/2018/6536919
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Enzymatic Screening of Micromeria fruticosa serpyllifolia Volatile Oils Collected from Three Different Regions of West Bank, Palestine

Abstract: Introduction Volatile oils (VOs) have been commonly used in cosmetics and food as fragrances, flavoring, and preservative agents or in alternative medicine for their therapeutic effects. This necessitates investigating those plants and their VOs. This study was conducted to investigate the chemical compositions of the VOs of Micromeria fruticosa serpyllifolia growing widely in three regions in Palestine (i.e., Hebron, Ramallah, and Nablus districts representing south, middle, and north of West Bank). Afterward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(43 reference statements)
0
6
0
1
Order By: Relevance
“…Volatile oils of the three samples of M. fruticosa serpyllifolia were extracted using microwave-ultrasonic apparatus; still, the results of this section can be obtained from the previously published work by the same research group [ 18 ]. However, these results are shown in Figure 1 modified from [ 18 ]. Briefly, Figure 1 represents the chemical composition obtained using GC-MS analysis in which the most abundant components in all three samples were pulegone and isomenthone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Volatile oils of the three samples of M. fruticosa serpyllifolia were extracted using microwave-ultrasonic apparatus; still, the results of this section can be obtained from the previously published work by the same research group [ 18 ]. However, these results are shown in Figure 1 modified from [ 18 ]. Briefly, Figure 1 represents the chemical composition obtained using GC-MS analysis in which the most abundant components in all three samples were pulegone and isomenthone.…”
Section: Resultsmentioning
confidence: 99%
“…The authors of the current study conducted several tests on wild-growing M. fruticosa serpyllifolia in three regions in the West Bank area in Palestine. Part of these tests has been published previously [ 18 ]. Specifically, structural elucidation and identification of the chemical composition using the GC-MS analysis section represent shared results with this study, therefore elaborating and discussing some aspects linked to the findings of the published manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…viticina revealed weak porcine pancreatic lipase inhibitory activity with an IC 50 value of 501.18 ± 0.38 µg/mL compared to that of antiobesity available drug Orlistat (IC 50 = 12.3 ± 0.33 µg/mL). Salameh et al reported that EO of Micromeria fruticosa serpyllifolia leaves (Lamiaceae) exhibited potent antilipase activity with an IC 50 value of 39.81 µg/mL, which is better than that of S. viticina EO (IC 50 = 501.18 ± 0.38 µg/mL) [18].…”
Section: Discussionmentioning
confidence: 99%
“…Micromeria fruticosa (L.) Druce subsp. Serpyllifolia is a perennial aromatic shrub belongs to the Lamiaceae family and widely grown in the Mediterranean regions [4]. The plant is commonly used in folk medicine as a herbal infusion to alleviate many illnesses, such as abdominal cramps, diarrhea, colds, ocular infection, cardiac disorders and wounds [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The plant is commonly used in folk medicine as a herbal infusion to alleviate many illnesses, such as abdominal cramps, diarrhea, colds, ocular infection, cardiac disorders and wounds [5,6]. Few reports on M. fruticosa have confirmed its multi-therapeutic potentialities, such as anti-inflammatory, gastroprotective [7,8], analgesic [9], antiobesity and antidiabetic activities [4]. Moreover, the aqueous extract and the volatile oil of M. fruticosa were previously screened for their antitumor activities against human colon tumor cells (HCT-116) and mammary carcinoma F7 (MCF-7), however, the underlying mechanism was not explored [10].…”
Section: Introductionmentioning
confidence: 99%